2009
DOI: 10.1103/physreve.79.026302
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle assembly via the dewetting of patterned thin metal lines: Understanding the instability mechanisms

Abstract: Nanosecond pulsed laser heating was used to control the assembly of spatially correlated nanoparticles from lithographically patterned pseudo-one-dimensional nickel lines. The evolution of the nickel line instabilities and nanoparticle formation with a correlated size and spacing was observed after a series of laser pulses. To understand the instabilities that direct the nanoparticle assembly, we have carried out nonlinear time-dependent simulations and linear stability analysis based on a simple hydrodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 26 publications
6
105
0
1
Order By: Relevance
“…There has been long-standing interest in the capillarity and surface tension effects on morphological evolution in various materials systems, dating back to the work of Plateau 1 and Rayleigh 2 . Recently, pulsed-laser-induced dewetting of two-dimensional films 3-9 , one-dimensional lines and rings [10][11][12][13] , and lithographically patterned nanostructures 14,15 has demonstrated that understanding and controlling thin-film and Rayleigh-Plateau instabilities improves the ability to create organized metallic nanoparticle ensembles. Assembled particles have also been shown to "jump" or eject from one substrate and transfer to another depending on the energetics and dynamics of various laser-melted nanostructures [16][17][18] .…”
Section: Lettermentioning
confidence: 99%
“…There has been long-standing interest in the capillarity and surface tension effects on morphological evolution in various materials systems, dating back to the work of Plateau 1 and Rayleigh 2 . Recently, pulsed-laser-induced dewetting of two-dimensional films 3-9 , one-dimensional lines and rings [10][11][12][13] , and lithographically patterned nanostructures 14,15 has demonstrated that understanding and controlling thin-film and Rayleigh-Plateau instabilities improves the ability to create organized metallic nanoparticle ensembles. Assembled particles have also been shown to "jump" or eject from one substrate and transfer to another depending on the energetics and dynamics of various laser-melted nanostructures [16][17][18] .…”
Section: Lettermentioning
confidence: 99%
“…Liquid ribbons like these can be seen in everyday life, as on car windscreens or in breaking uniform fluid films. Their study is also important in applications like Direct-Write, 1-4 printed electronics, 5 and material functionalisation, 6 which are different kinds of micro-and nano-fluidics applications. 7 Knowledge of the stability properties of this system is of fundamental importance, either because the breakup into droplets is an unwanted phenomenon or because a regular rupture pattern is desired.…”
Section: Introductionmentioning
confidence: 99%
“…The price to pay is approximate nature of the results, in particular in the context of liquid metal films that are characterized by large contact angles and fast evolution that suggests that inertial effects (not included in the standard version of the long-wave framework considered here) may be relevant. However, despite the fact that all the assumptions involved in deriving long-wave approach are not strictly satisfied, one can obtain reasonably accurate results when using the long-wave approach to explain physical experiments -see, e.g., [17][18][19][20], or even when comparing to direct numerical solvers of Navier-Stokes equations [21].…”
Section: A Thin Film With Marangoni Effectmentioning
confidence: 99%
“…The non-dimensional parameters are then specified by K = κl s /γ 0 , D = 3γ T /(2γ 0 ), and κ is related to Hamaker' s constant, A, by A = 6πκh 3 * l 3 s . The reader is referred to Appendix A for the values of the material parameters used, to [22] for extensive discussion regarding inclusion of disjoining pressure in the long-wave framework, to [15,17,19] for the use of the long-wave in the context of modeling liquid metal films, and to [1][2][3] for the discussion of Marangoni effects in a variety of settings. The numerical solutions of Eq.…”
Section: A Thin Film With Marangoni Effectmentioning
confidence: 99%